Pengaruh Motivasi Kerja dan Work Life Balance Terhadap Kepuasan Kerja Karyawan Bagian Keuangan Non ASN Sekretariat DPRD Kota Cimahi - Sheila Arinda; Juddy Prabowo (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The most important thing for an institution is human resource management. Good job satisfaction will have a positive impact on the institution, in improving employee job satisfaction by observing employee work motivation and work-life balance. From the findings of the data on tardiness and absenteeism, it can be seen that there is a high rate of unexplained absenteeism among employees in the finance department of the Cimahi City DPRD Secretariat. This investigation purposes to identificate how much work-life balance and work motivation, both separately and together, impact employees’ job satisfaction in the Cimahi City DPRD Secretariat’s non-civil servant financial separation. This is a quantitative study with respondents being all 33 non-civil servant employees in the finance department of the Cimahi City DPRD Secretariat. Questionnaires with a semantically distinct scale for measurements were employed for gathering data, and SPSS version 27 was utilized as a data processing tool for descriptive and associative methods of data analysis. Both work motivation and work-life balance have a favorable impact on employee job satisfaction, according to the findings of this study. Additionally, the job satisfaction of non-ASN finance department employees at the Cimahi City DPRD Secretariat is influenced by both work motivation and work-life balance at the same time.